2000
DOI: 10.1021/ma000443n
|View full text |Cite
|
Sign up to set email alerts
|

CO2-Induced Stereocomplex Formation of Stereoregular Poly(methyl methacrylate) and Microcellular Foams

Abstract: Crystalline stereocomplex formation of isotactic poly(methyl methacrylate) (it-PMMA) and syndiotactic poly(methyl methacrylate) (st-PMMA) induced by high-pressure CO2 at pressures in the 5−35 MPa range and at temperatures in the 30−110 °C range was demonstrated by means of differential scanning calorimetry (DSC) and wide-angle X-ray scattering (WAXS) investigations as a function of treatment pressure, temperature, and the it-PMMA/st-PMMA ratio. At a constant it-PMMA/st-PMMA ratio, the melting temperature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 79 publications
6
60
0
2
Order By: Relevance
“…23,25,28,36,37 Figure 1 shows the DSC thermograms of L-PLA and B-PLA at AP and various CO 2 pressures. At AP, both L-PLA and B-PLA had a broad cold crystallization peak at around 124°C and a melting peak at around 150°C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…23,25,28,36,37 Figure 1 shows the DSC thermograms of L-PLA and B-PLA at AP and various CO 2 pressures. At AP, both L-PLA and B-PLA had a broad cold crystallization peak at around 124°C and a melting peak at around 150°C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In accordance with the classical nucleation theory, the cell density and the bubble shape are affected by the foaming pressure or pressure sharp drop during foaming process. In all related researches, it has been demonstrated that the number of cells per unit volume increases and the average cell size decreases by subjecting the matrix to a larger pressure decline [14,15,18,25]. Contrary to the foaming pressure, the effects of foaming temperature on the cell morphology have not been understood precisely.…”
Section: Effects Of Foaming Temperaturementioning
confidence: 99%
“…Similarly, there are some reports about clay reinforced nanocomposite foams based on semicrystalline polymers [5][6][7][8]. Moreover, microcellular foaming process is one of the techniques that have been studied for this purpose [9][10][11][12][13][14][15][16]. By rapid pressure quenching [17], melt blending using polymers with high glass tran-sition temperature (T g ) [4] and incorporating nanoclay into polymers [7], micron or submicron size cellular structures have been successfully obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Smaller spherulites have been observed for poly(L-lactic acid)/PMMA blends exposed to CO 2 at 0°C and 10 MPa for 1 h. [126] The CO 2 -induced crystallization improves the mechanical properties and increases the heat distortion temperature relative to cold-crystallized blends without loss of transparency. Mizumoto and co-workers [127][128][129] have studied the formation of crystalline stereocomplexes composed of stereoregular isotactic PMMA (iPMMA, semicrystalline) and syndiotactic PMMA (sPMMA, amorphous) upon exposure to scCO 2 . The heat of fusion and T m of the stereocomplex both increase substantially with increasing CO 2 pressure up to 10 MPa.…”
Section: Scco 2 -Induced Crystallization/meltingmentioning
confidence: 99%
“…However, in some systems, crystalline structures can assist foaming. For example, the dissolution of CO 2 into a blend of iPMMA/sPMMA leads to the formation of crystalline stereocomplex structures, [127] which aid foaming by i) providing surfaces on which heterogeneous nucleation can proceed and ii) increasing the melt strength of the amorphous matrix to limit cell growth. The resulting cells are smaller (1.76 to 0.26 lm in diameter) and more dense (9.5 × 10 10 to 2.1 × 10 13 cells cm À3 ) in the crystallized blend than in amorphous sPMMA, as depicted in Figure 12.…”
Section: Cells CM à3mentioning
confidence: 99%